Dietary fiber inclusion as an alternative to Feed Fasting to induce molting in Commercial Layers - Sgavioli, S [UNESP]; Filardi, R Da S [UNESP]; Praes, M F F M [UNESP]; Domingues, C H De F [UNESP]; Pileggi, J [UNESP]; Andrade, P De C [UNESP]; Boleli, I C [UNESP]; Junqueira, O M [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2013)
The objective of the present experiment was to compare the performance, egg quality and organ morphometrics of commercial layers submitted to alternative forced molting methods using dietary fibers. The experimental period included the phases of molting, rest, and second laying cycle (six periods of 28 days each). In the trial, 320 commercial Isa Brown layers with 72 weeks of age were distributed, according to a completely randomized experimental design into five treatments with eight replicates of eight birds each, totaling 40 experimental units. Molting was induced by feeding diets with the inclusion of alfalfa or soybean husks at 80% and 60% or feed fasting. Treatments were applied for 14 days. Performance and egg quality parameters were evaluated for the second laying cycle and organ morphometrics (liver, gizzard, proventriculus, reproductive apparatus) in two different slaughter dates. The obtained data were submitted to analysis of variance using the General Linear Model (GLM) procedure of SAS statistical package (SAS Institute, 2002). Alternative molting methods promoted similar performance and egg quality results after molting were similar to those obtained by the conventional fasting method. Feeding fiber produced the expected effects in terms of organ weight regression and recovery and may be used to induce molting in commercial layers.
Keywords: Alfalfa; soybean husks; egg production; morphometrics